Mapping active gene-regulatory regions in human repopulating long-term HSCs - Wünsche, Peer; Eckert, Elias Simon Peter; Fronza, Raffaele; Gil-Fariña, Irene; Schmidt, Manfred; Kalle, Christof von; Herbst, Friederike; Glimm, Hanno (Cell stem cell, 2018)
Summary Genes that regulate hematopoietic stem cell (HSC) self-renewal, proliferation, and differentiation are tightly controlled by regulatory regions. However, mapping such regions relies on surface markers and immunophenotypic definition of HSCs. Here, we use γ-retroviral integration sites (γRV ISs) from a gene therapy trial for 10 patients with Wiskott-Aldrich syndrome to mark active enhancers and promoters in functionally defined long-term repopulating HSCs. Integration site clusters showed the highest ATAC-seq signals at HSC-specific peaks and strongly correlated with hematopoietic risk variants. Tagged genes were significantly enriched for HSC gene sets. We were able to map over 3,000 HSC regulatory regions in late-contributing HSCs, and we used these data to identify miR-10a and miR-335 as two miRNAs regulating early hematopoiesis. In this study, we show that viral insertion sites can be used as molecular tags to assess chromatin conformation on functionally defined cell populations, thereby providing a genome-wide resource for regulatory regions in human repopulating long-term HSCs.